2017
DOI: 10.1038/srep45218
|View full text |Cite
|
Sign up to set email alerts
|

First order reversal curves and intrinsic parameter determination for magnetic materials; limitations of hysteron-based approaches in correlated systems

Abstract: The generic problem of extracting information on intrinsic particle properties from the whole class of interacting magnetic fine particle systems is a long standing and difficult inverse problem. As an example, the Switching Field Distribution (SFD) is an important quantity in the characterization of magnetic systems, and its determination in many technological applications, such as recording media, is especially challenging. Techniques such as the first order reversal curve (FORC) methods, were developed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…figure 4) that are difficult to interpret physically, and they complicate analysis of multiple component samples. Physically, these extra features cannot fully be due to the interaction fields, but they have been previously shown to be potentially from thermal fluctuations [51]. Other magnetic measurements, such as ferromagnetic resonance, have shown that interaction fields cause broadening and/or shifts of the P Hc peak [52][53][54][55], but not necessary inducing extra local minima/maxima.…”
Section: Resultsmentioning
confidence: 97%
“…figure 4) that are difficult to interpret physically, and they complicate analysis of multiple component samples. Physically, these extra features cannot fully be due to the interaction fields, but they have been previously shown to be potentially from thermal fluctuations [51]. Other magnetic measurements, such as ferromagnetic resonance, have shown that interaction fields cause broadening and/or shifts of the P Hc peak [52][53][54][55], but not necessary inducing extra local minima/maxima.…”
Section: Resultsmentioning
confidence: 97%
“…These coordinates are defined as follows In such a coordination system, h c represents the local coercive field of each hysteron, and h u corresponds to the local interaction field shifting the hysteron’s center along the field axis. 41 The obtained FORC distributions ρ( h c , h u ) for both ascending and descending magnetization branches, together with FORC curve families M ( H R , H ) plotted in canvas of the hysteresis loop, are shown in Figure 6 . In each FORC distribution, there are two main prominent features related to the irreversible magnetization switching processes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It should be pointed out that in easy-axis NW arrays, the bias fields are positive [42,43]. In the mean-field framework [20,44,45], the interaction field H int is proportional to the magnetization den-sity: H int = kM/V = kPM s m, where k is a constant, m the reduced magnetization, P the film porosity and V the film volume. In the case of dipolar interactions, the demagnetizing field felt by a NW from the film mean magnetization density leads to k = +1/2 for the easy-plane case, instead of k = −1 for the easy-axis case [46,47].…”
Section: Coercive Field Distribution In the Easy Planementioning
confidence: 99%